2022
DOI: 10.1093/oncolo/oyac046
|View full text |Cite
|
Sign up to set email alerts
|

Inequity in Telemedicine Use Among Patients with Cancer in the Deep South During the COVID-19 Pandemic

Abstract: Background Telemedicine use has increased significantly during the COVID-19 pandemic. It remains unclear if its rapid growth exacerbates disparities in healthcare access. We aimed to characterize telemedicine use among a large oncology population in the Deep South during the COVID-19 pandemic. Materials and Methods A retrospective cohort study was performed at the only National Cancer Institute designated-cancer center in Ala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 27 publications
3
15
1
Order By: Relevance
“…In our study, females indicated lower preferences to use telehealth in the future; this is contrary to other reports that demonstrated that female cancer patients had greater satisfaction with telehealth during the COVID-19 pandemic [ 9 , 47 ]. These studies, however, did not focus on patients’ preferences for telehealth when provided with a choice between in-person and virtual visits in the future.…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, females indicated lower preferences to use telehealth in the future; this is contrary to other reports that demonstrated that female cancer patients had greater satisfaction with telehealth during the COVID-19 pandemic [ 9 , 47 ]. These studies, however, did not focus on patients’ preferences for telehealth when provided with a choice between in-person and virtual visits in the future.…”
Section: Discussioncontrasting
confidence: 99%
“…It is likely that these differences are the result of variable patient numbers and power to obtain statistical significance given the magnitude of odds ratios shown in Fig 3 (also S1 Appendix ). Our findings in the aggregate analysis of all oncology visits resulted in similar findings to those of Shao et al who studied a population from an NCI designated cancer center in the state of Alabama (in a population with greater minority representation than that seen in our study population) and found that patients of color were less likely to use video visits [ 29 ]. This supports the concern that telehealth might exacerbate existing inequities in healthcare and cancer care specifically if countermeasures are not developed [ 19 ].…”
Section: Discussionsupporting
confidence: 86%
“…Outside of oncology, analyses across primary and specialty practices have shown that older adults are less likely to participate in video visits [ 22 , 28 ]. A study of patients at another cancer center similarly found that older individuals were less likely to use video visits [ 29 ]. In a previous non-oncology focused analysis from our institution during a shorter time frame than that outlined in our manuscript, the mean ages for video visit users, phone visit users, and non-telehealth users were 42, 56, and 41, respectively [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Retrospective cohort study found that lower income areas as well as adults aged 85 years or older were more likely to use phone visits over video visits, however lack of digital and cellular access proved to be a common challenge. 18 Practicality in the developing world is also questionable. A recent review of telemedicine in Sub‐Saharan Africa demonstrates clear barriers including insufficient technological infrastrucutre and medical equipment, digital illiteracy, inaccessibility to medical care and financial barriers with lack of adquate funding.…”
Section: Introductionmentioning
confidence: 99%